Efficacy, Safety and Tolerability of High dose Valsartan Hydrochloride in Essential Hypertension - Zaman, MA (Cardiovascular Journal, 2013)
Background: Studies across the world have demonstrated the efficacy of valsartan in lowering blood pressure in a variety of patient populations, several of them investigated higher doses of the drug. This study focuses on revealing safety and efficacy of valsartan at higher doses in Bangladeshi population. Current study is planned to evaluate the efficacy, safety and tolerability of daily dose of Valsartan 160 or 320 mg in the treatment of essential hypertension. Method: This is a multi-center, open-label, observational, non-comparative, clinical decision based titration, involving about 31 centers in Bangladesh. A total of 334 newly diagnosed adult patients with essential hypertension received valsartan at a dose of 160 mg or 320 mg as deemed necessary by physician were included to allow for an assessment of efficacy, safety and tolerability. The total duration of treatment with valsartan was 16 weeks. Primary parameter for efficacy was percentage responders to valsartan at 16 weeks, reduction in Mean sitting systolic blood pressure (MSSBP) and Mean sitting Diastolic blood pressure MSDBP, control rate (% patients) achieving SBP <140 mmHg and DBP <90 mmHg at end point and Global assessment of efficacy and tolerability to valsartan treatment by the physician and patient. Result: Mean age of the patient was 53.31±8.8 years and 56.5% were male. A clearly evident decline is evident in mean Systolic BP and diastolic BP over the study duration. Average reduction of 30.4 ± 17.4 mmHg was seen in systolic BP, 18.4 ± 11.2 mmHg in diastolic BP and 3.5 ± 3.1/ minute in heart rate. The reduction was highly significant in both systolic BP and diastolic BP and heart rate as well (P<.001). At 16 weeks only 3.4% were found to be refractory to the treatment. Global assessment of safety and efficacy was assessed on four point scale, around 30.2% of the physician rated the efficacy as excellent, around 56% rated as very good and 13.8% rated as good. Tolerability of the treatment was also assessed based on the opinion of the patient and physician concerned on four point scale. Around 34.1% of the physician rated the tolerability as excellent, around 49.7% rated as very good and 16.2% rated as good. Conclusion: Sixteen week treatment with valsartan at 160mg daily or 320 mg daily is an effective treatment for patients with essential hypertension. The drug is found to be well tolerated with minimal adverse event during the course of treatment. DOI: http://dx.doi.org/10.3329/cardio.v5i2.14323 Cardiovasc. j. 2013; 5(2): 182-189